How to Get a Grip on Processes of Communalization and Distinction in Group Interactions—An Analytical Framework - Weiser-Zurmühlen, Kristin (Frontiers in Psychology, 2022)
This article proposes an analytical framework that combines Conversation Analysis, Positioning Theory, and Stance Analysis to study communalization and distinction as basic interactive mechanisms within group interactions. The framework is based on the premise that participants in multi-party interactions constantly manage the local demands of the ongoing conversation and turn-by-turn talk as well as implicitly or explicitly evoked references to global discourses, which in turn are closely related to the topic currently discussed. By considering both micro- and macro-contextual features in the analysis of group interactions, it is possible to reach a deeper understanding of dynamic group activities. The framework has been empirically developed based on data from a study on epistemic positioning practices in adolescents’ group interactions about popular TV series in Germany. The data comprises ten videotaped focus group discussions that have been elicited in a school context. By applying the framework to the analysis of a single case from the corpus, insights can be gained, both on how group members’ finely adjust their epistemic and evaluative stances as well as on how the participants themselves interactively link their stances to broader discourses.